Time to Viral Rebound After Interruption of Modern Antiretroviral Therapies. (12th June 2021) - Li, Jonathan Z; Aga, Evgenia; Bosch, Ronald J; Pilkinton, Mark; Kroon, Eugène; MacLaren, Lynsay; Keefer, Michael; Fox, Lawrence; Barr, Liz; Acosta, Edward; Ananworanich, Jintanat; Coombs, Robert; et al.
Abstract: Background: Development of human immunodeficiency virus (HIV) remission strategies requires precise information on time to HIV rebound after treatment interruption, but there is uncertainty regarding whether modern antiretroviral therapy (ART) regimens and timing of ART initiation may affect this outcome. Methods: AIDS Clinical Trials Group (ACTG) A5345 enrolled individuals who initiated ART during chronic or early HIV infection and on suppressive ART for ≥2 years. Participants underwent carefully monitored antiretroviral interruption. ART was restarted upon 2 successive viral loads ≥1000 copies/mL. We compared participants of A5345 with participants of 6 historic ACTG treatment interruption studies. Results: Thirty-three chronic-treated and 12 early-treated participants interrupted ART with evaluable time to viral rebound. Median time to viral rebound ≥1000 HIV RNA copies/mL was 22 days. Acute retroviral rebound syndrome was diagnosed in 9% of the chronic-treated and none of the early-treated individuals. All participants of the historic studies were on older protease inhibitor-based regimens, whereas 97% of A5345 participants were on integrase inhibitor-based ART. There were no differences in the timing of viral rebound comparing A5345 versus historic studies. In a combined analysis, a higher percentage of early-treated participants remained off ART at posttreatment interruption week 12 (chronic vs early: 2% vs 9%, P  = .0496). One chronic-treated and one early-treated A5345 participant remained off ART for >24 weeks. All participants resuppressed after ART reinitiation. Conclusions: Early ART initiation, using either older or newer ART regimens, was associated with a significant delay in the time to HIV rebound after ART interruption, lowering the barrier for HIV remission. Abstract : In A5345, we detected no differences in the timing of viral rebound with modern versus historic ART. Early ART was associated with a significant delay in the time to HIV rebound after ART interruption, lowering the barrier for HIV remission.